THE ROLE OF GRAMMAR IN IMPROVING STUDENTS’ WRITING SKILLS - Alimardonova Malika Botir qizi (Scholar Express Journals, 2021)
The variety of methodological approaches can contribute to improving students’ writing in educational institutions and there has always been a demand for predominant strategies. However, the role of grammar is essential not only in improving students’ writing abilities but also in other language skills, such as listening, reading and speaking. The question of making the way students write better has been significantly researched over the last few years. The current article investigates the urgency and actuality of grammar (in our case the English Grammar) in improving students’ writing. In the era of globalization, English is a very important tool in communication, especially when it is in a written form. Therefore, it is an essential prerequisite for students to master grammar to put their ideas and thoughts on paper. Consequently, teaching grammar in harmony with writing should be adapted to achieve proficiency in students’ writing abilities.
Keywords: Grammar skill, writing class, enhance, accuracy, students writing, writing instruction, peer editing, academic